1994
DOI: 10.1177/014920639402000302
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Advance Notice of Plant Closings on Firm Value

Abstract: The issue of workers displaced because of plant closings gained prominence in the 1980’S because of their growing numbers. With the increased attention focused on plant closings, the topic of advance notice has also gained prominence. This paper examines the issue of advance notice for plant closings and its effect on firm value. The findings of this study indicate that longer periods of advance notice have significant negative effects on firm value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…One set of studies uses the event study methodology to assess the short-run financial impact (abnormal returns) when firms engage in socially responsible or irresponsible acts (see, for example, Clinebell and Clinebell, 1994;Hannon and Milkovich, 1996;Posnikoff, 1997;Teoh, Welch and Wazzan, 1999;Worrell, Davidson, and Sharma, 1991;Wright and Ferris, 1997). The results of these studies have been mixed.…”
Section: Empirical Studies Of Csr and Financial Performancementioning
confidence: 99%
“…One set of studies uses the event study methodology to assess the short-run financial impact (abnormal returns) when firms engage in socially responsible or irresponsible acts (see, for example, Clinebell and Clinebell, 1994;Hannon and Milkovich, 1996;Posnikoff, 1997;Teoh, Welch and Wazzan, 1999;Worrell, Davidson, and Sharma, 1991;Wright and Ferris, 1997). The results of these studies have been mixed.…”
Section: Empirical Studies Of Csr and Financial Performancementioning
confidence: 99%
“…Cochran and Wood (1984) reexamined the relationships between corporate social responsibility and financial performance, and they found that exclusion of asset turnover and asset age led to spurious positive correlations between CSR and financial performance, and with this variable included; there is still weak evidence of positive correlation between the CSR and financial value. Mostly, there are two types of empirical studies of the relationship between the CSR and financial value (Clinebell and Clinebell, 1994;Hannon and Milkovich, 1996;Posnikoff, 1997;Teoh, Welch, and Wazzan, 1999;Worrell, Davidson, and Sharma, 1991;Wright and Ferris, 1997). Some studies use the event study methodology to assess the short-run financial impact (abnormal returns) when firms engage in socially responsible or irresponsible acts, and the results of these studies have been mixed.…”
Section: Research Questionmentioning
confidence: 99%
“…The studies dealt with several but again narrow issues ranging from development of affi rmative action programs ( Wright et al ., 1995 ), disinvestments in South Africa in the age of apartheid ( Meznar et al ., 1994 ;Teoh et al ., 1999 ;Posnikoff, 1997 ;Wright and Ferris, 1997 ), plant closures ( Clinebell and Clinebell, 1994 ) and lawsuits over discrimination ( Wright et al ., 1995 ) to the announcement of withdrawal of a product ( Davidson and Worrell, 1992 ) or failure to comply with the law ( Frooman, 1997 ). McWilliams et al .…”
Section: The Convergence Of the Empirical Researchmentioning
confidence: 99%